Teori Perdagangan Internasional: Pemahaman Konseptual dan Implikasinya Dalam Konteks Global - Adisty Maharani Purba; Anastasya C.L.S; Mhelinda Utami; Nelda Saparianti; T.Bahtazar Muhammad Sinar; Hafiza Adlina (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This journal discusses conceptual understanding of international trade theory and its implications in a global context. Theories such as absolute advantage, comparative advantage, Hecksher-Ohlin, and mercantilism are explained to understand the factors that drive international trade and the profits that can be made. In addition, barriers to international trade, such as protectionism and other factors, are also considered. In a global context, understanding international trade theories and overcoming these barriers is important to maximize the benefits of international trade and achieve sustainable economic growth.